Margarete Susman e i saggi sul femminile - Lozzi, Giuliano (Biblioteca di Studi di Filologia Moderna, 2015)
Margarete Susman (1872-1966), an important figure in German-speaking culture, was an essayist, Kulturtheoretikerin, philosopher, poet and painter. Her vast production - almost unknown in Italy - deals with a variety of topics: from literary criticism to interreligious dialogue, from the study of Romanticism to portraits of great personalities from the past and her time. This book investigates the 'feminine' in Susman from two points of view: from a formal perspective, it describes the path of a writer who, from the early 20th century, has moved between poetry and the essay, passing through the comparison with culture correspondence; from a thematic perspective, he examines the essays in which Susman deals with the sexual difference and the relationship between the 'male' and the 'female'.